Academic Research Consortium High Bleeding Risk Criteria associated with 2-year bleeding events and mortality after transcatheter aortic valve replacement discharge: a Japanese Multicentre Prospective OCEAN-TAVI Registry Study. Issue 3 (15th November 2021) - Mizutani, Kazuki; Nakazawa, Gaku; Yamaguchi, Tomohiro; Ogawa, Mana; Okai, Tsukasa; Yashima, Fumiaki; Naganuma, Toru; Yamanaka, Futoshi; Tada, Norio; Takagi, Kensuke; Yamawaki, Masahiro; Ueno, Hiroshi; et al.
Abstract: Aims: To investigate the ability of the Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria and ARC-HBR score to predict 2-year bleeding and mortality in patients undergoing transcatheter aortic valve replacement (TAVR). Methods and results: We enrolled 2514 patients who underwent successful TAVR during 2013–17. In this study, we used the ARC-HBR score for further HBR-risk stratification, and the ARC-HBR score was calculated as follows: each major criterion was 2 points and each minor criterion was 1 point. The impact of the ARC-HBR criteria and increasing ARC-HBR score on the incidence of moderate/severe bleeding events, mortality, and ischaemic stroke in the first 2 years were evaluated. We used survival classification and regression tree (CART) analysis for 2-year moderate or severe bleeding events, and patients were statistically classified into HBR low- (ARC-HBR score ≤1), intermediate- (ARC-HBR score = 2–4), or high-risk (ARC-HBR score ≥5) groups, and 91.4% were at HBR (ARC-HBR score ≥2). The rates of 2-year moderate/severe bleeding events and all-cause mortality were higher in the ARC-HBR group and highest in the HBR high-risk group. An increased HBR score was significantly associated with moderate/severe bleeding events [hazard ratio (HR) 1.19, 95% confidence interval (CI) 1.07–1.31; P = 0.001] and all-cause mortality (adjusted HR 1.24, 95% CI 1.17–1.32; P < 0.001). Conclusions: The ARC-HBR criteria identify patients at HBR after TAVR; an increased ARC-HBR score is associated with 2-year moderate/severe bleeding events and mortality. Graphical Abstract: